Structural distortion and temperature-dependent carrier transport of Al-, Ga-, and In-doped ZnO thin films - Trang Thuy Thi Phan; Oanh Kieu Truong Le; Hoa Thi Lai; Quang Thua Trieu; Thu Bao Nguyen Le; Vinh Cao Tran; Thang Bach Phan; Anh Tuan Thanh Pham (Vietnam Journal of Science, Technology and Engineering, 2025)
ZnO-based films hold significant potential for optoelectronic applications, such as transparent electrodes and absorbance layers, as well as thermoelectric applications. Doping with Al, Ga, and In has attracted considerable attention for controlling the carrier transport properties of these films. Pure ZnO, Al-doped ZnO, Ga-doped ZnO, and In-doped ZnO films, each with a similar doping ratio of 1 wt%, were successfully deposited on glass substrates using the magnetron sputtering technique. X-ray diffraction was employed to confirm the ZnO structure, while temperature-dependent Hall-effect measurements were utilised to investigate the dependence of carrier transport on temperature. The results indicate that Al and Ga dopants enhance conductivity more effectively than In. This may be attributed to a substantial increase in carrier concentration when Al and Ga are doped into ZnO-based films as the temperature rises. Conversely, the In-doped ZnO film exhibits an increase in mobility, resulting in enhanced conductivity. These findings underscore the intricate interplay between doping elements, measurement temperature, and the electrical behaviour in ZnO films, offering valuable insights for further optimisation and application in various electronic and optoelectronic devices. This research opens the possibility of controlling the properties of ZnO films for applications at different operating temperatures.